2008
DOI: 10.1899/07-044r.1
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships of atyid shrimps imply both ancient Caribbean radiations and common marine dispersals

Abstract: The evolutionary relationships of the surface genera of shrimps of the family Atyidae from the Caribbean were inferred using mitochondrial 16S ribosomal DNA and cytochrome oxidase I gene sequences. The genetic divergence among the 4 Caribbean genera (Atya, Jonga, Micratya, Potimirim) is extensive and dates from between the Eocene and Miocene. This result suggests a vicariant origin or the ancient dispersal of some taxa. Most intrageneric divergences date to the late Miocene-Pliocene and, thus, are probably the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 56 publications
1
46
0
18
Order By: Relevance
“…Jonga serrei (Bouvier, 1909) Distribution: Cuba; Jamaica; Puerto Rico; Dominica; Barbados; Costa Rica (Chace and Hobbs 1969); Guadeloupe (Lévêque 1974); Venezuela (Pereira 1991); Tobago (Page et al 2008); Panama: Bocas del Toro (present study), being the first record for the country.…”
Section: Site N°additional Field Notesmentioning
confidence: 54%
See 1 more Smart Citation
“…Jonga serrei (Bouvier, 1909) Distribution: Cuba; Jamaica; Puerto Rico; Dominica; Barbados; Costa Rica (Chace and Hobbs 1969); Guadeloupe (Lévêque 1974); Venezuela (Pereira 1991); Tobago (Page et al 2008); Panama: Bocas del Toro (present study), being the first record for the country.…”
Section: Site N°additional Field Notesmentioning
confidence: 54%
“…It was found sympatrically with Atya scabra, Micratya poeyi and Macrobrachium acanthurus at site 13 and with Jonga serrei at site 12 (see Table 2). This species was also found in Río Guarumo (Cabbage Creek), about 16 km from Chiriquí Grande (Page et al 2008).…”
Section: Site N°additional Field Notesmentioning
confidence: 77%
“…Amphidromous (ELD) species generally have broader geographic ranges than non-amphidromous species in the same taxon. Gene flow among populations of the same species tends to be greater in amphidromous or presumed (small egg size) amphidromous species (Page et al, 2005(Page et al, , 2008Cook et al, 2006;Mashiko & Shy, 2008). For example, Mashiko & Shy (2008) studied four species of Macrobrachium in the western Pacific.…”
Section: Evolutionary Origins Of Amphidromymentioning
confidence: 99%
“…Dennenmoser et al (2010) demonstrated, using haplotypes of a mitochondrial gene, high gene flow among separate river populations over a distance of several hundred kilometers. The biogeography and distributional patterns of Caribbean and Pacific atyid shrimps appears, in large part, to be a product of larval dispersal or lack thereof (Page et al, 2008;Cook et al, 2009Cook et al, , 2012. "Estuary hopping" (larval movement among nearby estuaries), or limited dispersal in the open sea, has allowed gene flow among IndoAustralian populations of the river shrimp Macrobrachium rosenbergii (De Bruyn & Mather, 2007).…”
Section: Evolutionary Origins Of Amphidromymentioning
confidence: 99%
“…As larvae develop in estuaries or the open sea, dispersal to adjacent and sometimes distant streams and rivers, sometimes on other land masses, can occur. A variety of studies on populations of amphidromous species show gene flow among populations from stream systems on the same or other land masses (Page et al, 2005(Page et al, , 2007(Page et al, , 2008Cook et al, 2006;Mashiko & Shy, 2008). Amphidromy allows colonization of new but similar habitats as well as recruitment back into the stream of larval origin (Hunte, 1978).…”
Section: Costs Benefits and Origins Of Amphidromy In Shrimpsmentioning
confidence: 99%